IMPLEMENTASI E-GOVERNMENT BAGI KETERBUKAAN INFORMASI PUBLIK MELALUI WEBSITE PEMERINTAH KABUPATEN MANGGARAI - Guntur, Walburga Nofri; Tuan, Yohanes; Asnawi, Norani (Petitum Law Journal, 2025)
This article analyzes the implementation of public information disclosure through the website of the Manggarai Regency Government, in terms of the principle of openness in state administration law. This research also identifies the obstacles and impacts of public information disclosure implementation on local government accountability. The research method used is empirical law with a juridical and qualitative approach. Primary data was collected through interviews and questionnaires from officials of the Communication and Information Office and the public who access the website. Secondary data was obtained from literature review, laws and regulations, website documentation, and related research reports. The results show that the implementation of public information disclosure has not been optimal. The quality of information and website updates need to be improved, not fully fulfilling the principles of openness. The internal obstacles are limited human resources and lack of coordination between OPDs. External barriers are inadequate technological infrastructure and low public awareness of public information disclosure. As a result, government accountability is affected, public trust decreases, and there is potential for disinformation and cyber security threats.